Scholarly Communication, Open Access Publishing, and Research Visibility in Nigerian and Sub-Saharan African Universities (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Nigerian universities produce a substantial volume of research across disciplines such as agriculture, public health, education, governance, and the humanities; however, much of this scholarship remains underrepresented in global academic communication systems. This paper examines the structural conditions shaping scholarly communication in Nigerian and Sub-Saharan African universities, with particular emphasis on open access (OA) publishing as a mechanism for improving research visibility. Drawing on a systematic review of literature and institutional data from OpenDOAR, African Journals OnLine (AJOL), and the National Universities Commission (NUC), the study analyzes the effectiveness and limitations of gold, green, diamond, and bronze OA models within the Nigerian context.The findings reveal persistent barriers to OA adoption, including the high cost of article processing charges (APCs), weak institutional repository infrastructure, the absence of coordinated national OA policies, and the growing challenge of predatory publishing. These constraints collectively reduce the global discoverability of Nigerian research and reinforce structural inequities in scholarly communication. Despite these challenges, emerging opportunities are identified, including the expansion of AJOL as a continental OA platform, the potential of diamond OA models supported by scholarly societies, and the strategic role of institutional repositories in enhancing access and visibility.The paper concludes by proposing a national OA strategy aligned with UNESCO’s Open Science framework, emphasizing policy reform, repository mandates, and sustainable funding models to strengthen the visibility and impact of Nigerian and African scholarship.